Kenakalan Remaja Di SMA Negeri 2 Tarutung - Elisa Martina Barus (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Youth involvement in deviant behavior, including violence and bullying, is a major problem in education in Indonesia, particularly in SMN 2 Tarutung. The purpose of this study was to determine the different types of juvenile delinquency and analyze the components that contribute to these behaviors. Data were collected through observations, surveys and in-depth interviews with students and teachers using a qualitative approach with a case study design. The results showed that juvenile delinquency includes serious behaviors such as substance abuse and promiscuity to minor discipline violations. Negative interactions with peers, an unsupportive family environment, and students' disengaged attitudes with school are some of the influential factors. The impact of this delinquency creates an unfavorable environment for learning.